Understanding Acehnese Proverbs and Their Relation to the Community Work Ethics - Mursyidin Mursyidin; Rahmad Nuthihar; Wahdaniah Wahdaniah; RN Herman (Universitas Teuku Umar, 2020)
This study discusses the work ethic of the Acehnese people based on hadih maja(Acehnese proverb). This research used qualitative descriptive approach. Sources of the data come from a collection of Acehnese proverbs written by Hasyim (1977) and interviews with the community regarding the use of Acehnese proverbs. The results of this study suggest that the work ethics of the people of Aceh can be categorized based on five attitudes which include (1) responsibility, (2) hard work, (3) rational, (4) honest, and (5) discipline. The form of responsibility includes doing the job completely and not giving the job to someone else. Hard work is described by not wasting time but utilizing time productively. Rational attitude is described by doing logical work and being able to do well. Honesty must be carried out by workers in order to obtain safety in and trust from others. Furthermore, discipline is illustrated by the routine of the Acehnese people who demand to work on time.